2017
DOI: 10.14260/jemds/2017/1268
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and Biofilm Formation Among Nosocomial Pathogens in a Tertiary Care Hospital

Abstract: BACKGROUNDBiofilm formation is an important mode of growth because it is associated with the chronic nature of the subsequent infections, and it helps in inherent resistance to antibiotic chemotherapy. Various nosocomial infections which are associated with the indwelling devices are the source as their surfaces become a niche for biofilm producing microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…10 Among the S. aureus , the overall MRSA prevalence in our study was 33.6% which was lower than studies from various centers across India where the prevalence rates vary from 38.6% to 52%. 15 16 17 Moreover, we observed that the MRSA prevalence rose from 29.5% in 2016 to 35% in 2018. This pattern was very similar to the recent reports which highlighted that over a decade, the MRSA prevalence has gradually escalated from 29% in 2009 18 to 39% in 2018.…”
Section: Discussionmentioning
confidence: 73%
“…10 Among the S. aureus , the overall MRSA prevalence in our study was 33.6% which was lower than studies from various centers across India where the prevalence rates vary from 38.6% to 52%. 15 16 17 Moreover, we observed that the MRSA prevalence rose from 29.5% in 2016 to 35% in 2018. This pattern was very similar to the recent reports which highlighted that over a decade, the MRSA prevalence has gradually escalated from 29% in 2009 18 to 39% in 2018.…”
Section: Discussionmentioning
confidence: 73%
“…6,18 While the majority of the work has been done on materials in which the A site is fully occupied by either 3+ (Ru 4+ ) or 2+ (Ru 5+ ) cations, there are few studies reporting the effect of having a mixed oxidation state on the A site. 1,2 Doping the A sites with 2+ cations could result in a hole doping effect concomitant with an increased concentration of disordered oxygen vacancies in these oxides; 19,20,21,22,23 this is expected to provide them with the required ionic conductivity to be used as cathodes in IT-SOFC. 24,25,26,27,28,29 In this work, we present a study of the physical properties of Y2-xZnxRu2O7 (Zn 2+ doped system).…”
Section: Introductionmentioning
confidence: 99%
“…yang menunjukkan proporsi isolat A. baumannii resisten multiobat penghasil biofilm sebesar 54.1% dengan metode tabung dari 74 berbagai isolat sampel klinis yang berasal dari peralatan medis yaitu kateter vena sentral, kateter urin, ETT, tracheostomy tubes dan chest drain tube tips dari pasien rawat jalan dan rawat inap. (19) Hasil yang lebih rendah ditunjukkan dari penelitian yang dilakukan oleh de Campos. dkk yaitu sebesar 44% isolat…”
Section: Pendahuluanunclassified